Upaya Hukum yang Dilakukan Korban Kejahatan Dikaji dari Perspektif Sistem Peradilan Pidana dalam Putusan Mahkamah Agung Republik Indonesia - Lubis, Muhammad Ridwan (Universitas Ekasakti, 2023)
The state, via the Institute for the Protection of Witnesses and Victims (LPSK), leads the way in addressing crime victim compensation as a means of fulfilling state obligations and securing the welfare of the populace. LPSK stands for the Witness and Victim Protection Agency, an organization mandated with safeguarding the rights and safety of witnesses and/or victims. In accordance with the Law Number 13 of 2006 concerning Witness and Victim Protection, LPSK guarantees equal legal certainty. Compensation is regulated in Law Number 13 of 2006 jo. Article 28D paragraph (1) of the 1945 Constitution emphasizes that